Acromegaly: The Research and Practical Value of Noninvasive Hemodynamic Assessments via Impedance Cardiography - Jurek, Agnieszka; Krzesiński, Paweł; Gielerak, Grzegorz; Witek, Przemysław; Zieliński, Grzegorz; Kazimierczak, Anna; Wierzbowski, Robert; Banak, Małgorzata; Uziębło-Życzkowska, Beata (Frontiers in Endocrinology, 2022)
Background Arterial hypertension (AH) that accompanies acromegaly (AC) may lead to cardiovascular dysfunction. Such consequences may be detected with impedance cardiography (ICG), which is a noninvasive method of hemodynamic assessment. Early detection of subclinical hemodynamic alterations in AC patients may be crucial for optimizing treatment and preventing cardiovascular remodeling. The purpose of this study was to identify the hemodynamic parameters of the cardiovascular system that differentiate patients with AC from those in the control group (CG), with a particular emphasis on potential targets for medical therapy. Methods This observational, prospective, clinical study involved a comparative analysis of 33 AC patients with no significant comorbidities and the controls selected via propensity score matching based on a set of baseline characteristics (age, sex, body mass index, mean blood pressure [MBP]), with comparable proportions of AH patients. The assessed hemodynamic parameters included the stroke volume index (SI), cardiac index, systemic vascular resistance index, velocity index (VI), acceleration index, Heather index (HI), and thoracic fluid content (TFC). Results Both the AC group and the CG had well-controlled AH (mean blood pressure of 121/77 mmHg and 119/76 mmHg, respectively). In terms of baseline characteristics, the AC group was characterized by a higher hear rate and lower creatinine levels than the CG (76.2 bpm vs. 66.8 bpm [p = 0.001] and 0.755 mg/dL vs. 0.850 mg/dL [p = 0.035], respectively). ICG assessment of AC patients and CG patients showed the former to have higher heart rates (73.5 bpm vs. 65.2 bpm; p = 0.003), lower SI (43.8 mL/m2 vs. 53.4 mL/m2; p = 0.0001), lower VI (42.1 1/1000/s vs. 49.3 1/1000/s; p = 0.037), lower HI (8.49 Ohm/s2 vs. 13.4 Ohm/s2, p ≤ 0.0001), and higher thoracic fluid content (TFC) (38.4 1/kOhm vs. 28.1 1/kOhm; p ≤ 0.0001), respectively. Conclusions Even with well-controlled hypertension, AC is associated with a high TFC, increased heart rate, and decreased indices of cardiac contractility. Hemodynamic changes in AC patients may be detected with the modern, noninvasive diagnostic tool, ICG.